Forcing boundary-layer transition on an inverted airfoil in ground effect and at varying incidence - Roberts, L.; Finnis, Mark V.; Knowles, Kevin; Lawson, Nicholas J. (AIAA, 2016)
The influence of the laminar boundary-layer state on a wing operating in ground effect at Re = 6 × 10 has been investigated using experiments with a model that provides two-dimensional flow and computations with a panel-method code. The effect of a boundary-layer trip placed at varying distances from the leading edge was observed at various incidences in terms of on-surface characteristics, including pressure measurements, flow visualisation and hot-film anemometry, and off-surface characteristics with LDA surveys below and behind the wing. The act of forcing transition led to downforce being reduced and drag increased, moreover, it altered almost all aspects of the wing’s aerodynamic characteristics, with the effect becoming greater as the trip was placed closer to the leading edge. These aspects include the replacement of a laminar separation bubble with trailing-edge separation, a thicker boundary layer, and a thicker wake with greater velocity deficit. The importance of considering laminar phenomena for wings operating in ground effect has been shown
Presented at 34th AIAA Applied Aerodynamics Conference